The combination of holmium laser and ALA-PDT for Bowenoid Papulosis with diffuse large B-cell lymphoma - Jiawen Gao; Haiyan Zhang; Zhongxia Zhou; Xiaofei Sun; Guolong Zhang; Peiru Wang; Xiuli Wang (Photodiagnosis and Photodynamic Therapy)
Bowenoid Papulosis (BP) is an anogenital pre-malignancy. BP with immunosuppression may recur, worsen, or possibly evolve into squamous cell carcinoma or Bowen's disease (BD), and it may also become resistant to conventional treatment. Here, we describe a complex case of BP together with BD and Diffuse Large B-Cell Lymphoma that was effectively treated with a holmium laser in conjunction with 5-Aminolevulinic Acid Photodynamic Therapy (ALA-PDT). The lesion totally vanished and the affected area remained intact with no recurrence at five years.